Draft Genome Sequence of Aeromonas caviae UFMG-H8, Isolated from Urine from a Healthy Bovine Heifer (Gyr Breed) - Giannattasio-Ferraz, Silvia (Microbiol Resour Announc, 2020)
Aeromonas caviae is an emerging pathogen in humans, causing intestinal infections. Here, we report Aeromonas caviae strain UFMG-H8, isolated from the urine of a healthy heifer (Gyr breed).